Tetramer‐visualized gluten‐specific CD4+ T cells in blood as a potential diagnostic marker for coeliac disease without oral gluten challenge. Issue 4 (1st August 2014) - Christophersen, Asbjørn; Ráki, Melinda; Bergseng, Elin; Lundin, Knut EA; Jahnsen, Jørgen; Sollid, Ludvig M; Qiao, Shuo-Wang
Abstract : Background: Diagnosing coeliac disease (CD) can be challenging, despite highly specific autoantibodies and typical mucosal changes in the small intestine. The T‐cell response to gluten is a hallmark of the disease that has been hitherto unexploited in clinical work‐up. Objectives: We aimed to develop a new method that directly visualizes and characterizes gluten‐reactive CD4+ T cells in blood, independently of gluten challenge, and to explore its diagnostic potential. Methods: We performed bead‐enrichment of DQ2.5‐glia‐α1a and DQ2.5‐glia‐α2 tetramer+ cells in the blood of control individuals, treated (TCD) and untreated patients (UCD). We visualized these cells by flow cytometry, sorted them and cloned them. We assessed their specificity by antigen stimulation and re‐staining with tetramers. Results: We detected significantly more gliadin‐tetramer+ CD4+ effector memory T cells (TEM ) in UCD and TCD patients, compared to controls. Significantly more gliadin‐tetramer+ TEM in the CD patients than in controls expressed the gut‐homing marker integrin‐β7. Conclusion: Quantification of gut‐homing, gluten‐specific TEM in peripheral blood, visualized with human leukocyte antigen (HLA) ‐tetramers, may be used to distinguish CD patients from healthy individuals. Easy access to gluten‐reactive blood T cells from diseased and healthy individuals may lead to new insights on the disease‐driving CD4+ T cells in CD.